Wiring design using elec software / Mohamad Embong - Embong, Mohamad (1992)
The main objective of this project is to know how to run the software, inserting the correct data input and to store the additional protective characteristic data from various manufactures. In this report theoretical and practical part of wiring design was discussed. This report was based on Elec software <15 th Edition) that produced by Hevacomp U.K on December 1390. Elec software is just one of the program for Mechanical and Electrical Design Package (Building Services). The main Elec package enables us to complete electrical system of sub-mains, boards and final circuits to be set-up , size and checked.